Tissue factor and tissue factor pathway inhibitor levels in trophoblast cells: implications for placental hemostasis - Aharon, Anat; Brenner, Benjamin; Katz, Tamar; Miyagi, Yohei; Lanir, Naomi (Thrombosis and Haemostasis, 2004)
The placenta is a highly vascularized organ with fetal and maternal blood supply. Syncytiotrophoblasts (STB), which line the placenta villous are possibly involved in local hemostatic mechanisms.The aim of this study was to evaluate the levels of tissue factor (TF) and its inhibitors, tissue factor pathway inhibitor (TFPI,TFPI-2), in STB model within hemostatic and inflammatory environments. Human primary STB cell cultures were characterized by vascular and hormonal markers. TF and TFPI mRNA expression, protein levels and activity were determined and compared to human umbilical vein endothelial cells (HUVEC). High levels of TF were demonstrated in STB cells compared to low levels in HUVEC. In contrast, STB expressed lower TFPI levels than HUVEC. LPS and TNFα increased the high constitutive TF in STB, whereas LPS and IL-1α further reduced TFPI levels. The procoagulant tendency of STB identified by us may reflect the physiological need for immediate inhibition of hemorrhage in the placental inter-villous spaces in basal and inflammatory conditions.This hemostatic balance may be critical for normal placental function and pregnancy outcome.
Keywords: Tissue factor; tissue factor pathway inhibitor (TFPI); placenta; trophoblast; inflammation